Children Under 5 Years as Predicting Dengue Transmission in Kebumen District, Indonesia: Case Study Mapping Approaches - Nugroho Susanto; M. Dody Izhar; Frans Manangsang (Masters Program in Public Health, 2025)
Background: Dengue disease is still a problem in the world. Factors affecting population main importance for dengue transmission. The dengue cases severity 34.40% in Indonesia, and the study area is an endemic dengue. The study aimed to determine factors causing dengue transmission in the Kebumen district, Central Java Province.Subjects and Method: A cross-sectional study was conducted in 460 villages in Kebumen district, Central Java. The study was conducted in 2024 by taking dengue data from medical records in the period January 2023 to December 2023. The number of dengue cases during the study period was 395 cases that were diagnosed. The dependent variable is transmission zone. The status village transmission is a number of dengue cases> 2 cases in the village during the study based on medical records. The independent variables are children under 5 years, the incidence rate of dengue, the incidence rate area, the incidence rate density, and population age > 70 years (elderly). Data of dengue cases were obtained from medical record. The data were analyzed with an independent t-test, linear regression test, and survival test (Cox proportional hazards).Results: The incidence rate averaged 30.17 higher than the government standard, with 10 cases/ 100,000 population for each village, and was higher in March. The population, density, children under 5 years, elderly upper 70 years, incidence density, incidence case, incidence areas, and large no significant differences between village transmission and no transmission p≤0.050, and variable contributing to dengue transmission R2= 0.39 or 39.20%. The hazard time for infection (HR = 0.62; CI95%= 0.46 to 0.83).Conclusion: The zone is high risk for dengue transmission, 24.6% of the 460. The factors significantly related to dengue transmission in the village as population size, population density, children under 5 years, elderly upper 70 years, incidence density, incidence case, and incidence area contributing to dengue transmission, R2= 0.39. The main factor contributing to dengue transmission is incidence density, β= 69.95.